MSMES INTEREST IN THE USE OF SHARIA E-PAYMENT: EXPANDED IMPLEMENTATION OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Agustina, Ike Dwi; Wahidiyah, Rahmatul 'Aini; Misbahuddin, Abdullah Afif; Ningtyas, Mega Noerman; Budianto, Eka Wahyu Hestya (Institut Teknologi dan Bisnis Asia Malang, 2024)
Advances in technology and information encourage the development of payment methods using electronic devices (e-payment) to exchange goods and services without needing cash. This study examines the factors that influence the interest of MSMEs in Malang City, especially in the culinary field, in using Sharia e-payments by expanding the TAM model. This type of research is descriptive quantitative. The survey used a structural equation model (SEM) with the Amos software test tool (Versi 26). One hundred twenty-five respondents were collected as a test. The results show that PS has an insignificant effect on PU and PEOU. PEOU influences PU. PFC has a significant negative effect on Islamic e-payment IU. PU has no significant effect on the IU of Sharia e-payments. Meanwhile, PEOU influences IU Sharia e-payments.